Cosmopolitan ideals? From the Reign of Liberty to the assumption of necessity. A Feminist Reading from the South - Ciriza, Alejandra (2024)
Under the conjecture that embodied people draw expectations of emancipation on the basis of a certain historical horizon, this work investigates the limits and pressures that the current conditions of existence imprint on the political imagination of those who inhabit the south of the planet, at a time of increase in inequalities between human beings and aggression against the nature that we are and in which we live. This work traces, from a situated and feminist perspective, some significant temporal milestones because these marks in time account made possible a cosmopolitan horizon, in which we can take notice that the world with which we stay, in which we live, is one.  Under the sign of the French Revolution, Kant constructed the idea of a cosmopolitan government and imagined a norm for regulating relations between states that would enable a hospitality capable of welcoming the stranger as a full subject of law. Under the imprint of 1848 (and also of 1871) Marx projected, from the terrain of history and class struggle, the possibility of an emancipation that could be international. The world today shows a desolate panorama: the globalization of the world with its aftermath of reification and commodification of nature, with the bet on war in its different versions as a way out of the capitalist crisis, with fierce competition for what has become scarce: fuel, land, water, seeds. Cosmopolitanism, as an ethical and political imperative, invites us to take on the challenge implied by the impossibility of reproducing life on the planet under the current conditions of capitalist globalization. The cosmopolitan horizon can no longer be the realm of abstract freedom, but that of the assumption of the determinations of the realm of necessity: dependence on the nature that we are and in which we live, the importance of the body, the need for food, affection, care that human been can only satisfy in community.